Callus formation and plant regeneration from protoplasts of sunflower calli and hypocotyls - Conceição Santos; Gustavo Caldeira (Acta Societatis Botanicorum Poloniae, 2014)
Sunflower (cv. Girapac SH222) protoplasts were obtained from 4-7 day-old hypocotyls and cotyledons and from two-month old calli. Higher yields of protoplasts were achieved with medium El (KCl 25g dm-3, CaCl2 2g dm-3, MES 0.7 g• dm-3, pH 5.5) and the combination of Driselase Fluka 0.2%, Macerozyme Onozuka 0.2% and Cellulase Onozuka R10 0.2%. Hypocotyls gave the highest yields of protoplasts, followed by cotyledons and calli. Protoplasts were cultivated in liquid and on solid media using both L4M (Burrus et al., 1991) and V-KM (Bokelman and Roest, 1983) media. Culture on solid M1 medium (L4M medium supplemented with NAA 3.0 mg•dm- 3, 2,4-D 0.1 mg•dm-3 and BA 1.0 mg•dm -3) gave a good planting efficiency with the development of many white-green colonies. These colonies gave rise to small calli which were transferred to MSmod medium (MS medium supplemented with KCI 5 g•dm-', and polyvinylpyrrolidone (PVP, 4 g• dm-3) containing benziladenine (BA, 0.5 mg•dm-3), naphtaleneacetic acid (NAA, 0.5 mg•dm-3) and giberelic acid (GA3 0.1 mg•dm-3). After two weeks, calli were transferred to MSmod medium containing BA 1.0 mg•dm-3, NAA 0.1 mg•dm-3, and GA3 0.1 mg•dm-3 for shoot formation. Shoots were excised and induced to root in MSmod supplemented with BA 0.1 mg•dm-3, NAA 1.0 mg•dm-3, and GA3 0.1 mg•dm-3. Plantlets were then transferred to sterilised vermiculite for greenhouse acclimation.